Prevention and Detection Methods for Enhancing Security in an RFID System - Jing Huey Khor; Widad Ismail; Mohammad Ghulam Rahman (International Journal of Distributed Sensor Networks)
Low-cost radio frequency identification (RFID) tag is exposed to various security and privacy threats due to computational constraint. This paper proposes the use of both prevention and detection techniques to solve the security and privacy issues. A mutual authentication protocol with integration of tag's unique electronic fingerprint is proposed to enhance the security level in RFID communication. A lightweight cryptographic algorithm that conforms to the EPCglobal Class-1 Generation-2 standard is proposed to prevent replay attack, denial of service, and data leakage issues. The security of the protocol is validated by using formal analysis tool, AVISPA. The received power of tag is used as a unique electronic fingerprint to detect cloning tags. t -test algorithm is used to analyze received power of tag at single-frequency band to distinguish between legitimate and counterfeit tag. False acceptance rate (FAR), false rejection rate (FRR), receiver operating characteristic (ROC) curve, and equal error rate (EER) were implemented to justify the robustness of t -test in detecting counterfeit tags. Received power of tag at single frequency band that was analyzed by using t -test was proved to be able to detect counterfeit tag efficiently as the area under the ROC curve obtained is high (0.922).